Transformational Leadership Style Analysis at PT. Tomo Food Industry Sumedang - Ade Mumuh Muchlis Taufik; Helles Amanda; Shinta Rizqiya (Journal of Bussines Management Basic, 2022)
Leadership is the art of leading, because each person's approach to leading people can differ depending on the characteristics of the leader, the characteristics of the task and the characteristics of the person they lead. This study aims to find out how the implementation of transformational leadership styles, constraints and solutions in applying transformational leadership styles to the PT. Tomo Food Industri Sumedang. This research method uses qualitative research methods. The sampling technique uses purposive sampling technique with employees as research informants. Data collection is done by means of observation, interviews, and documentation. The research data were analyzed using the miles and Huberman model analysis method. With the stages of data collection, data reduction, data presentation and data conclusion. The results showed that transformational leadership carried out at PT. Tomo Food Industri is good. These results are shown by the behavior of leaders who have a strategy in leading a clear company, have a concern to solve problems by deliberation, stimulate company members to always work together by positioning themselves as partners and always maintain team cohesiveness with a polite and humble attitude, so as to create major changes both in subordinates and organizations in achieving goals. Based on the analysis of the data obtained from various informants, it can be concluded that the Transformational leadership style at PT. Tomo Food Industry has done very well by implementing a clear strategy by positioning itself as a partner. By giving some suggestions for the future to pay more attention to their employees by enforcing rewards and punishments